Mechanisms of immunothrombosis in COVID-19. Issue 6 (November 2021) - Portier, Irina; Campbell, Robert A.; Denorme, Frederik
Abstract : Purpose of review: Coronavirus disease 2019 (COVID-19) is an infectious disease caused by severe acute respiratory syndrome coronavirus-2. Over the past year, COVID-19 has posed a significant threat to global health. Although the infection is associated with mild symptoms in many patients, a significant proportion of patients develop a prothrombotic state due to a combination of alterations in coagulation and immune cell function. The purpose of this review is to discuss the pathophysiological characteristics of COVID-19 that contribute to the immunothrombosis. Recent findings: Endotheliopathy during COVID-19 results in increased multimeric von Willebrand factor release and the potential for increased platelet adhesion to the endothelium. In addition, decreased anticoagulant proteins on the surface of endothelial cells further alters the hemostatic balance. Soluble coagulation markers are also markedly dysregulated, including plasminogen activator inhibitor-1 and tissue factor, leading to COVID-19 induced coagulopathy. Platelet hyperreactivity results in increased platelet-neutrophil and -monocyte aggregates further exacerbating the coagulopathy observed during COVID-19. Finally, the COVID-19-induced cytokine storm primes neutrophils to release neutrophil extracellular traps, which trap platelets and prothrombotic proteins contributing to pulmonary thrombotic complications. Summary: Immunothrombosis significantly contributes to the pathophysiology of COVID-19. Understanding the mechanisms behind COVID-19-induced coagulopathy will lead to future therapies for patients.